Intellectual disability in patients with epilepsy with eyelid myoclonias - Maria Arvio; Oili Sauna-aho; Timo Nyrke; Nina Bjelogrlic-Laakso (SAGE PUBLICATIONS INC, 2025)
We describe here the clinical outcome of four women with epilepsy with eyelid myoclonia (aged 21-53years). All patients had an uneventful early history, normal physical growth and appearance and no comorbid sensory or motor disability and normal brain magnetic resonance imaging finding. Two women were moderately and one mildly intellectually disabled and one showed a low-average intelligence. The overall well-being of the patients was hampered by psychiatric or various somatic comorbidities and related psychosocial problems. The three women with an intellectual disability had been treated with narrow-spectrum antiepileptic drugs and one also with vigabatrin during childhood and adolescence. The patient with a low-average intelligence had been on broad-spectrum antiepileptic medication (i.e. valproate and ethosuximide) since the epilepsy diagnosis but she has had compliance problems. Based on these cases, the cognitive deficits in patients with epilepsy with eyelid myoclonia may occur more commonly than what has been thought hitherto. We discuss the role of narrow-spectrum antiepileptic drugs as a contributing factor to poor seizure control and an impaired intelligence.